Studies on chemical constituents and antifungal activity of leaf essential oil of Lippia alba (Mill) - Rao, G. P. (2000)
The leaf volatile oil of Lippia alba (Mill) has been analysed by GC and GC-MS. Fifty components have been identified accounting for about 90% of the total oil. The major constituent is geranial (15.57%) followed by a unresolvable mixture of myrthenol and myrthenal (9.89%), neral (9.44%), geraniol (7.36%), 2,6-octadien-1-o l, 3,7-dimethyl acetate (6.87%), 1-octene-3-ol (4.66%),6-methyl-5-hepten-2-one (4.60%), caryophyllene oxide (4.52%), β-caryophyllene (3.09%), citronellol (2.63%), linalool (2.20%), 3-pinene-2-o l (2. 19%), β-myrcene (1.49%), farnesol (1.35%) and spathulenol. It was also found that oil vapours possessed strong antifungal activity against sugarcane pathogens. The oil was highly effective in controlling teleutospore germination of Ustilago scitaminea and conidial germination of Colletotrichum falcatum and Curvularia lunata at 3×103 μl/L concentration. The oil also proved superior in comparison to commercial fungicides in controlling plant pathogenic fungi.